2010
DOI: 10.1038/bmt.2010.261
|View full text |Cite
|
Sign up to set email alerts
|

Signature profiles of CMV-specific T-cells in patients with CMV reactivation after hematopoietic SCT

Abstract: Depletion of cellular immunity as a consequence of conditioning before allogeneic hematopoietic SCT (HSCT) frequently results in CMV reactivation, which may in turn lead to life-threatening infections and require timely antiviral treatment. We have investigated the functional signatures of CMV-specific CD4 þ and CD8 þ T-cells in 191 samples from 118 individuals. We compared healthy donors with both patients with high and undetectable viral loads, and those who controlled and did not control their CMV reactivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 47 publications
2
40
0
Order By: Relevance
“…Our findings are consistent, however, with a prior study by Lilleri et al who also found that polyfunctional CMV-specific T cells producing IFNγ and IL-2 were associated with protection (43). In addition, the increase of MFI values of IFNγ with decreased CMV-specific CD8 + polyfunctionality in PBSC recipients at day 30, aligns with the work of Krol et al, who suggested that production of IFNγ alone may be a sign of T cell exhaustion during viral infection (44). We recently showed, using CMV-specific tetramers, that HCT patients with ≥ 7 positive tetramer cells per mL in at least one blood sample before day 65 post-transplant were statistically protected from CMV infection (45), although the protection was not complete.…”
Section: Discussionsupporting
confidence: 86%
“…Our findings are consistent, however, with a prior study by Lilleri et al who also found that polyfunctional CMV-specific T cells producing IFNγ and IL-2 were associated with protection (43). In addition, the increase of MFI values of IFNγ with decreased CMV-specific CD8 + polyfunctionality in PBSC recipients at day 30, aligns with the work of Krol et al, who suggested that production of IFNγ alone may be a sign of T cell exhaustion during viral infection (44). We recently showed, using CMV-specific tetramers, that HCT patients with ≥ 7 positive tetramer cells per mL in at least one blood sample before day 65 post-transplant were statistically protected from CMV infection (45), although the protection was not complete.…”
Section: Discussionsupporting
confidence: 86%
“…All analyzed CVID-AcT patients presented detectable levels of a CMV IL-10 homolog, which was concordant with the presence of a CMV-specific T-cell response (data not shown). CMV persistence was confirmed in 8 out of 9 CVID-AcT patients and in 11 out of 15 other CVID patients by intracellular cytokine staining after CMV peptide stimulation, as described previously3233.…”
Section: Resultsmentioning
confidence: 99%
“…Polyfunctional T cells, capable of the simultaneous production of multiple cytokines, have been associated with improved immunological control across many acute and chronic viral infections, including CMV (Betts et al 2006;Darrah et al 2007;Krol et al 2011;Sauce et al 2016). Recently, Chiu et al described that a higher degree of cytotoxicity-associated polyfunctionality was positively correlated with a larger total CMV-specific response size, both for CD8+ and CD4+ CMV responses (Chiu et al 2016).…”
Section: T Cell Polyfunctionality and CMV Responsesmentioning
confidence: 99%